Transient camptocormia with citalopram treatment in a patient with mixed dementia-A case report - Inbal Segal; Galia Fisher RN; Doron Merims (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
This case report reviews a patient who suffered mixed dementia with depression. The addition of citalopram to the medication regimen was shortly followed by the manifestation of camptocormia, or "bent-spine." Clinical findings available, without attempting invasive diagnostic procedures, point to a citalopram induced camptocormia. The frequent use of SSRI medications in the geriatric population call for an increased awareness of the possibility of SSRI induced postural side effects.